Effects of Isokinetic Training on Trunk Muscle Fitness and Body Composition in World-Class Canoe Sprinters - Zinke, Fridolin; Warnke, Torsten; Gäbler, Martijn; Granacher, Urs (Frontiers in Physiology, 2019)
In canoe sprint, the trunk muscles play an important role in stabilizing the body in an unstable environment (boat) and in generating forces that are transmitted through the shoulders and arms to the paddle for propulsion of the boat. Isokinetic training is well suited for sports in which propulsion is generated through water resistance due to similarities in the resistive mode. Thus, the purpose of this study was to determine the effects of isokinetic training in addition to regular sport-specific training on trunk muscular fitness and body composition in world-class canoeists and to evaluate associations between trunk muscular fitness and canoe-specific performance. Nine world class canoeists (age: 25.6±3.3 years; 3 females; 4 world champions; 3 Olympic gold medalists) participated in an 8 week progressive isokinetic training with a 6 week block “muscle hypertrophy” and a 2 week block “muscle power”. Pre- and post-tests included the assessment of peak isokinetic torque at different velocities in concentric (30&140°s-1) and eccentric (30&90°s-1) mode, trunk muscle endurance, and body composition (e.g., body fat, segmental lean mass). Additionally, peak paddle force was assessed in the flume at a water current of 3.4 m/s. Significant pre-to-post increases were found for peak torque of the trunk rotators at 30°s-1 (p=.047; d=0.4) and 140°s-1 (p=.014; d=0.7) in concentric mode. No significant pre-to-post changes were detected for eccentric trunk rotator torque, trunk muscle endurance, and body composition (p>.148). Significant medium-to-large correlations were observed between concentric trunk rotator torque but not trunk muscle endurance and peak paddle force, irrespective of the isokinetic movement velocity (all r≥.886; p≤.008). Isokinetic trunk rotator training is effective in improving concentric trunk rotator strength in world-class canoe sprinters. It is recommended to progressively increase angular velocity from 30°s-1 to 140°s-1 over the course of the training period.